2015
DOI: 10.1186/s13023-015-0311-0
|View full text |Cite
|
Sign up to set email alerts
|

Naproxcinod shows significant advantages over naproxen in the mdx model of Duchenne Muscular Dystrophy

Abstract: BackgroundIn dystrophin-deficient muscles of Duchenne Muscular Dystrophy (DMD) patients and the mdx mouse model, nitric oxide (NO) signalling is impaired. Previous studies have shown that NO-donating drugs are beneficial in dystrophic mouse models. Recently, a long-term treatment (9 months) of mdx mice with naproxcinod, an NO-donating naproxen, has shown a significant improvement of the dystrophic phenotype with beneficial effects present throughout the disease progression. It remains however to be clearly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…However, it may not be the end for naproxcinod clinical development, since it recently received from FDA and European Medicines Agency (EMA) the orphan drug designation for the treatment of Duchenne muscular dystrophy . In fact, some animal studies have already shown the naproxcinod potential to delay the progression of muscular dystrophies . Furthermore, a recent agreement between NicOx and Fera Pharmaceuticals (USA) gives hope to the further development of naproxcinod to be commercialized in USA…”
Section: Association Of Nsaids With Protective Mediatorsmentioning
confidence: 99%
“…However, it may not be the end for naproxcinod clinical development, since it recently received from FDA and European Medicines Agency (EMA) the orphan drug designation for the treatment of Duchenne muscular dystrophy . In fact, some animal studies have already shown the naproxcinod potential to delay the progression of muscular dystrophies . Furthermore, a recent agreement between NicOx and Fera Pharmaceuticals (USA) gives hope to the further development of naproxcinod to be commercialized in USA…”
Section: Association Of Nsaids With Protective Mediatorsmentioning
confidence: 99%
“…The advancement also of NO-releasing prodrugs of other NSAIDs, such as Naproxen (compound 24, Figure 11) into late-stage clinical evaluation [54] illustrates the potential application of NO-releasing aspirin prodrugs if such a compound could be identified. Indeed, in 2015 compound 24 secured orphan drug designation from the FDA as a potential treatment for Duchenne Muscular Dystrophy [55,56].…”
Section: Figurementioning
confidence: 99%
“…For the assessment of skeletal muscle morphology, LAM/laminin, and hematoxylin and eosin (H & E) staining were performed as previously described [57,58]. For quantitative analysis, cross-sectional area (CSA) was analyzed in LAM/laminin-stained (see Table 1) muscle sections using ImageJ software.…”
Section: Histology and Morphometric Analysismentioning
confidence: 99%